1988
DOI: 10.1897/1552-8618(1988)7[35:uoscta]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Use of Selenastrum Capricornutum to Assess the Toxicity Potential of Surface and Ground Water Contamination Caused by Chromium Waste

Abstract: United Chrome Products, Inc. (Corvallis, OR), discharged liquid chrome-plating wastes into an on-site dry well from 1957 to 1977. Samples were collected from ground and surface waters during February and December 1984 and evaluated for toxicity potential using 96-h Selenastrum capricornutum bioassays. Bioassays of the February samples were used to calculate predicted EC50 values for different chromium concentrations, which %ere then compared with the chromium concentrations measured in the December samples and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

1992
1992
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 1 publication
0
7
0
1
Order By: Relevance
“…On the contrary, the EC,, values for the SRM low-level urine are lower than for the elevated urine. Zn concentration in the lowlevel urine is much higher (2.7 times) than in the elevated one, and higher than the EC50 value (30). The latter is not so for the elevated supposedly more toxic urine.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…On the contrary, the EC,, values for the SRM low-level urine are lower than for the elevated urine. Zn concentration in the lowlevel urine is much higher (2.7 times) than in the elevated one, and higher than the EC50 value (30). The latter is not so for the elevated supposedly more toxic urine.…”
Section: Discussionmentioning
confidence: 66%
“…Even with correction for the latter effects, interpretation of biological/environmental monitoring results may not be possible because of matrix effects in uncharacterized samples. However, the approach outlined in this paper is suggested for use in separating the effects of physical factors from those of chemical factors even though Greene et al, (30) suggest otherwise. Since environmental and biological samples are undefined mixtures in general, the initial bioassay results must of necessity include physical as well as chemical factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, EC50 flask assay values of 217 pg . L-' (confidence interval of 176-570) for Cr6+ (Greene et al, 1988), of 34 (Chiaudani and Vighi, 19781, 45 (Vasseur et al, 1988), and 23-37 pg * L-l for Cu2+ (Blaise et al, 19861, and of 27 (Chiaudani and Vighi, 1978), 54 t 11 (Vasseur et al., 1988) and 45 p g . L-l for Zn2+ (Blaise et al, 1986), have been reported.…”
Section: Reference Chemicalsmentioning
confidence: 99%